2012
DOI: 10.1111/eth.12036
|View full text |Cite
|
Sign up to set email alerts
|

Defence Cheats Can Degrade Protection of Chemically Defended Prey

Abstract: Many species defend themselves against enemies using repellent chemicals. An important but unanswered question is why investment in chemical defence is often variable within prey populations. One explanation is that some prey benefit by cheating, paying no costs of defence, but gaining a reduced attack rate because of the presence of defended conspecifics. Two important assumptions about predator behaviour must be met to explain cheating as a stable strategy: first, predators increase attack rates as cheats in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 35 publications
(54 reference statements)
1
17
2
Order By: Relevance
“…There are fewer examinations with wild predators, though Carroll and Sherratt (2013) recently demonstrated reduced damage to individual prey. In our own investigations with free living adult birds (Jones et al 2013) and mealworms as prey we found strong public benefits of reduced attack rates as chemical defence (a distasteful bitrex treatment) became more common, but we did not observe individual survival, in which defended prey are released before ingestion. Rather birds either ate the prey at the foraging site, or flew away from our feeding stations before deciding to eat or reject prey, making it difficult to determine whether, or the extent to which, individual prey benefitted from their chemical defence.…”
Section: Introductioncontrasting
confidence: 60%
See 3 more Smart Citations
“…There are fewer examinations with wild predators, though Carroll and Sherratt (2013) recently demonstrated reduced damage to individual prey. In our own investigations with free living adult birds (Jones et al 2013) and mealworms as prey we found strong public benefits of reduced attack rates as chemical defence (a distasteful bitrex treatment) became more common, but we did not observe individual survival, in which defended prey are released before ingestion. Rather birds either ate the prey at the foraging site, or flew away from our feeding stations before deciding to eat or reject prey, making it difficult to determine whether, or the extent to which, individual prey benefitted from their chemical defence.…”
Section: Introductioncontrasting
confidence: 60%
“…To examine whether the birds could to any extent discriminate mimics from models we used the method employed by Jones et al (2013), in which we determine the difference between the observed proportion of prey attacked that are defended with that expected by their frequency in the set of prey presented. We then used a one-tailed t test, to determine if the mean difference across birds was different from zero.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…from a food source. In our co-evolutionary model the inter-population diversification is a consequence of drift which is an interesting result: intra-population cheating (or automimicry) is problematic in the context of evolutionary stability as it undermines the effectiveness of the signal since cheating appears to be at a selective advantage [26]. Drift instead allows a wide diversity of inter-population aposematic solutions without the introduction of destabilising cheating or automimicry on the intra-population level.…”
Section: Discussionmentioning
confidence: 99%